“A particularly desirable exercise for girls and women”: Swimming and Modern Female Bodies in the United States, 1900s–1930s - Olaf Stieglitz (Angles)
Swimming in the USA was booming during the early 20th century. It held an important part in ongoing health and fitness debates, it was popular as a spare time activity, and many considered it as a particularly democratic sport. Moreover, and this marks the key argument of this essay, was swimming at that point charged with marking human bodies as explicitly ‘modern,’ as a practice that made normative notions and ideals of ability, competence and beauty especially visible. These attributions were closely linked to both gendered and racialized codes. Swimming, this essay argues, was supposed to create idealized male and female bodies. The development of the new crawl style stood at the center of that process. The article offers a close reading of the style’s genealogy within the American context. Next to photographs, it analyses swimming textbooks but also letters and reports written by young women swimmers that allow for a closer look at the actual practice of swimming and how it was part of negotiating modernity in the US.